PNSCares: The android based mobile application to manage student complaints - N. Illias; N. H. Abdul Hamid; Z. A. Shaffiei (Bulletin of Electrical Engineering and Informatics, 2020)
Managing the complaint is tough to handle, efficient response to the complaints from the customer can be an indicator to measure an organization’s performance. We’ve chosen Politeknik Nilai as one of the institutions that are facing daily complaints from the students and parents. Currently, they are using the manual form to lodge a complaint and receive the feedback via email. In this study, we developed an android based mobile application to manage the students’ complaint. With mobile apps, the management can prevent the loss of complaint forms and keep track of the records. This system will send feedback and notification directly via students’ mobile phone. This study referred to the ten principles for effective complaint handling by Ombudsman. We only referred to eight principles to construct the PNSCares. The methodology used to develop mobile apps is using the Mobile Application Development Life Cycle (MADLC). System Usability Scale (SUS) is used to measure the effectiveness of the mobile apps. The feedbacks from ten respondents on the PNSCares prototype are good with 72 scores in SUS for perceived usefulness and ease of use factor. Based on the result, the prototype is effective and easy to use.